2016
DOI: 10.2174/1874306401610010096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Exposure to High Particulate Levels on Cough Reflex Sensitivity in Healthy Tourists: A Pilot Study

Abstract: Background:Previous studies have reported a relationship between particulate air pollution and respiratory symptoms or decline in lung function, but information about acute effects of short-term exposure to airborne particulate matter (PM) on cough and pulmonary function is scarce.Objective:To investigate the effect of short-term exposure to high concentrations of PM on the cough reflex threshold, urge-to-cough, pulmonary function, and cough-related quality of life in a group of healthy non-resident volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…Further investigations are needed to confirm our speculation, given that transient receptor potential ankyrin-1 (TRPA1) rather than TRPV1 has been implicated in traffic-derived particulate matter eliciting cough 3637. Furthermore, short-time exposure to high concentrations of particulate matter in Beijing increases citric acid cough reflex sensitivity in healthy tourists 29. In the present study, however, only capsaicin cough challenge was analyzed.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Further investigations are needed to confirm our speculation, given that transient receptor potential ankyrin-1 (TRPA1) rather than TRPV1 has been implicated in traffic-derived particulate matter eliciting cough 3637. Furthermore, short-time exposure to high concentrations of particulate matter in Beijing increases citric acid cough reflex sensitivity in healthy tourists 29. In the present study, however, only capsaicin cough challenge was analyzed.…”
Section: Discussionmentioning
confidence: 79%
“…Rising levels of air pollution from industrial and traffic emissions have become a major threat to public health in China 28. It has been reported that pollutants can not only enhance cough reflex sensitivity, but also induce non-allergic eosinophilic airway inflammation 2930. In China, males account for over 80% of industrial workers31 and traffic police,32 as well as 95% of professional taxi33 and bus drivers,34 whose mean age was 37.6-38.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, air pollution level is more serious in China compared to western countries, the annual particulate matter 2.5 concentration was 31–44 ug/m 3 in the Pearl River Delta Region of China from 2013 to 2017 [ 17 ]. Short-term exposure to pollutants could evoke more cough among the patients with chronic obstructive pulmonary disease [ 18 ], while a decline of air pollution level was associated with a reduction in prevalence of chronic cough [ 19 ]. Furthermore, recent studies mentioned that diverse racial and geographic backgrounds, unhealthy lifestyle, occupational exposure, as well as dietary habit might contribute to these demographic discrepancies of chronic cough patients across different regions [ 7 , 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both human and animal studies have shown that ambient PM contributes to pulmonary inflammation through the induction of oxidative stress, influencing cell signalling pathways and production of inflammatory mediators, leading to inflammatory cell recruitment . Ambient PM inhalation also affects the autonomic nervous system (ie modulates heart rate variability ) and induces bronchoconstriction and cough by sensory nerve activation . In addition, ambient PM inhalation initiates airway inflammation by activation of irritant receptors and acid‐sensitive pathways located on sensory C nerve fibres lining the nasal and pulmonary airways.…”
Section: Air Pollution and Asthmamentioning
confidence: 99%
“…[81][82][83][84] Ambient PM inhalation also affects the autonomic nervous system (ie modulates heart rate variability 85 ) and induces bronchoconstriction and cough by sensory nerve activation. 86,87 In addition, ambient PM inhalation initiates airway inflammation by activation of irritant receptors and acid-sensitive pathways located on sensory C nerve fibres lining the nasal and pulmonary airways.…”
Section: Air Pollution and Asthmamentioning
confidence: 99%